2015
DOI: 10.1093/toxsci/kfv093
|View full text |Cite
|
Sign up to set email alerts
|

Ozone Inhalation Impairs Coronary Artery Dilation via Intracellular Oxidative Stress: Evidence for Serum-Borne Factors as Drivers of Systemic Toxicity

Abstract: Ambient ozone (O3) levels are associated with cardiovascular morbidity and mortality, but the underlying pathophysiological mechanisms driving extrapulmonary toxicity remain unclear. This study examined the coronary vascular bed of rats in terms of constrictive and dilatory responses to known agonists following a single O3 inhalation exposure. In addition, serum from exposed rats was used in ex vivo preparations to examine whether bioactivity and toxic effects of inhaled O3 could be conveyed to extrapulmonary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 51 publications
4
37
1
Order By: Relevance
“…Electron paramagnetic resonance (EPR) spectroscopy was conducted according to previously described methods with some modifications (Paffett et al , 2015). Following serum treatment, mCECs were incubated with the iron-chelate NO-spin trap Fe 2+- di( N -methyl- d -glutaminedithiocarbamate) (Fe 2+ (MGD) 2 ; 1mM, final concentration) for 5min.…”
Section: Methodsmentioning
confidence: 99%
“…Electron paramagnetic resonance (EPR) spectroscopy was conducted according to previously described methods with some modifications (Paffett et al , 2015). Following serum treatment, mCECs were incubated with the iron-chelate NO-spin trap Fe 2+- di( N -methyl- d -glutaminedithiocarbamate) (Fe 2+ (MGD) 2 ; 1mM, final concentration) for 5min.…”
Section: Methodsmentioning
confidence: 99%
“…However, the toxic effects of exposure to airborne total particulate matter (PM) from primary TRP have been demonstrated (1114). These toxic effects range from increased short-term morbidity in individuals with preexisting respiratory and cardiovascular disease to excess mortality rates over life-long exposure durations (15, 16).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous epidemiology studies have shown the association between ozone exposure and respiratory and cardiovascular diseases [2,5,29]. Inhaled ozone could cause decreased lung function and increased airway hyper-reactivity, particularly for those with preexisting conditions [11,30]. A recent study using the rat experiment model suggested that ozone exposure could lead to significant perturbations of coronary vascular functions possibly related to intracellular redox disturbances [31].…”
Section: Discussionmentioning
confidence: 99%